Bonding performance of universal adhesives with concomitant use of silanes to CAD/CAM blocks - Marina AMARAL; Jaqueline Maria Brandão RIZZATO; Victoria Caroline Souza de ALMEIDA; Priscila Christiane Suzy LIPORONI; Rayssa Ferreira ZANATTA (Faculdade São Leopoldo Mandic, 2023)
ABSTRACT Objective: This study assessed whether the use of a silane coupling agent influence the bond strength of two universal adhesives to ceramic or resin CAD/CAM blocks. Methods: Forty-eight samples were obtained from each resin nano-ceramic hybrid block (RCBs) and lithium disilicate ceramic blocks (LD). Samples were treated with silane with MDP (Monobond - S-MDP), silane without MDP (Prosil - PS), and no silane application (Control - Ctr) followed by universal adhesive with silane (UAS) and without silane (UA) (n=8). Three polyurethane tubes (1.5 mm of internal diameter) were positioned in each sample treated surface and filled with a dual cured resin cement. Bond strength was assessed by microshear bond strength test and failure analysis was performed for all samples. Results: For the RCBs, UAS presented the highest bond strength values (p=0.004). Silane application was not significant in bond strength values (p=0.444). For LD, silane application was significant in bond strength values (p<0.001), but the adhesive was not (p=0.066). Failure analysis showed high prevalence of adhesive failures for both substrates. Conclusion: A silane-containing universal adhesive promoted the best bond strength results to the resin nano-ceramic hybrid block. For bonding to a glass-ceramic CAD/CAM material, additional silane (without MDP) application presented the best results.